What is the importance of finishing and polishing in direct composite resin restorations in anterior teeth? (Research, Society and Development, 2022)
The search for aesthetic dental procedures has increased considerably in recent years. With the evolution of resins and direct restorative techniques, diastema closure can be performed, following a clinical protocol conducive to esthetics and restoration composting. This article presents the clinical sequence of diastema closure performed at the Clinic of the Federal University of Maranhão (UFMA). Seeking to emphasize the importance of obeying aesthetic and functional principles of the dental structure and periodontal tissues, emphasizing the importance of finishing and polishing in the success of mimicking the characteristics of natural teeth. It was possible to conclude that with the choice of suitable restorative materials and techniques, combined with a systematic protocol for finishing and polishing the composite resin, it is possible to provide the rehabilitated tooth with characteristics that bring it as close as possible to a natural tooth, favoring a higher quality and treatment longevity.